Cross Talk of pp125(FAK) and pp59(Lyn) Non-Receptor Tyrosine Kinases to Insulin-Mimetic Signaling in Adipocytes - Müller, Günter (American Society for Microbiology, 2000)
Signaling molecules downstream from the insulin receptor, such as the insulin receptor substrate protein 1 (IRS-1), are also activated by other receptor tyrosine kinases. Here we demonstrate that the non-receptor tyrosine kinases, focal adhesion kinase pp125(FAK) and Src-class kinase pp59(Lyn), after insulin-independent activation by phosphoinositolglycans (PIG), can cross talk to metabolic insulin signaling in rat and 3T3-L1 adipocytes. Introduction by electroporation of neutralizing antibodies against pp59(Lyn) and pp125(FAK) into isolated rat adipocytes blocked IRS-1 tyrosine phosphorylation in response to PIG but not insulin. Introduction of peptides encompassing either the major autophosphorylation site of pp125(FAK), tyrosine 397, or its regulatory loop with the twin tyrosines 576 and 577 inhibited PIG-induced IRS-1 tyrosine phosphorylation and glucose transport. PIG-induced pp59(Lyn) kinase activation and pp125(FAK) tyrosine phosphorylation were impaired by the former and latter peptide, respectively. Up-regulation of pp125(FAK) by integrin clustering diminished PIG-induced IRS-1 tyrosine phosphorylation and glucose transport in nonadherent but not adherent adipocytes. In conclusion, PIG induced IRS-1 tyrosine phosphorylation by causing (integrin antagonized) recruitment of IRS-1 and pp59(Lyn) to the common signaling platform molecule pp125(FAK), where cross talk of PIG-like structures and extracellular matrix proteins to metabolic insulin signaling may converge, possibly for the integration of the demands of glucose metabolism and cell architecture.